Pendidikan Akhlak Berbasis Tasawuf: Relevansi dan Implementasi dalam Konteks Pendidikan Modern - M. Nur, Faisal (LaKaspia, 2025)
This study aims to examine the relevance of Sufi values in moral education and to analyze the potential for their implementation within the framework of modern education. The background of this research is driven by the growing moral crisis in the midst of globalization and modernization, where education tends to emphasize cognitive aspects and technical skills while neglecting spiritual and moral dimensions. Sufism, with its orientation toward self-purification (tazkiyat al-nafs) and the cultivation of noble character, is considered a conceptual alternative capable of reinforcing the fundamental role of education in shaping the insān kāmil a holistic individual who is knowledgeable, virtuous, and possesses an integrated personality. The research method employed is library research, focusing on primary sources such as the works of classical Sufi scholars including al-Ghazali, al-Qushayri, and Ibn ‘Aṭā’illah, as well as secondary sources comprising books, journal articles, and scholarly publications related to moral education and the modernization of Islamic education. The data were analyzed using a descriptive-analytical approach, aimed at describing, critiquing, and synthesizing ideas derived from the literature. The findings indicate that Sufi-based moral education is highly relevant in addressing contemporary moral crises. Its implementation can be realized through value-based curricula, teachers’ moral exemplarity, spiritual habituation, and the creation of a school culture that emphasizes compassion, tolerance, and peace. Thus, Sufism is not only of spiritual significance but also offers practical applicability as a foundation for modern education.